The robustest clusters in the input-output networks: Global CO₂ emission clusters - Omar Rifki; Hirotaka Ono; Shigemi Kagawa (Journal of Economic Structures, 2017)
Finding environmentally significant clusters in global supply-chain networks of goods and services has been investigated by Kagawa et al. (Soc Netw 35(3):423-438, 2013a; Econ Syst Res 25(3):265-286, 2013b; Glob Environ Chang, 2015), using the popular clustering method of nonnegative matrix factorization, which actually yields sensitive cluster assignments. Due to this sensitivity issue, there is a danger of overfitting of the results. In order to confirm the robustness of the obtained clusters, which in fact have strong implications for international climate change mitigation, especially for the US-induced Chinese clusters, we design a simulation-based experiment. Empirical findings of the proposed approach are compared with those of Kagawa et al. (Glob Environ Chang, 2015). The environmental implications are reported as well.
Keywords: 330; Robustness; CO2 emissions; Cluster analysis; Simulation